Rodina: tussen lethargie en revolutie [Rodina: between lethargy and revolution] - Hoyte-West, Antony (Cappadocia Journal of Area Studies, 2021)
Review of Rodina: tussen lethargie en revolutie, by Arnout Brouwers (Amsterdam: Atlas Contact, 2018)